Optimal error estimate for the noncoercive quasivariational inequality with nonlinear source term related to impulse control problems - Nesrine Amari; Abida Harbi; Mohamed Haiour (Journal of Inequalities and Applications)
Abstract This paper deals with the numerical analysis of noncoercive quasivariational inequalities related to impulse control problems with nonlinear source term. The optimally L ∞ $L^{∞}$ -error estimate is derived by adopting an algorithmic approach.